PENENTUAN UMUR ABSOLUT BATUAN KUBAH LAVA ANDESIT DAERAH PANAS BUMI LEJJA-KABUPATEN SOPPENG, PROVINSI SULAWESI SELATAN MENGGUNAKAN METODE THERMOLUMINESCENCE (TL): DETERMINATION OF ABSOLUTE AGE LAVA DOME ANDESITE ROCK AT GEOTHERMAL LEJJA AREA, SOPPENG DISTRICT, SOUTH SULAWESI PROVINCE BY THERMOLUMINESCENCE (TL) METHOD - Risdianto, Dikdik; Sukaesih, Sukaesih; Nurdin, Nizar Muhamad; Situmorang, Stephen; Haryanto, Agus Didit (Buletin Sumber Daya Geologi, 2020)
Thermoluminescence (TL) has now been applied as a dating method for rock age. In geothermal exploration information about the age of rocks / volcanic material is very important to reconstruct the geological history related to thermal activity. Determination of the estimated age of rocks as a source of heat in the Lejja Geothermal prospect in Soppeng Regency, South Sulawesi Province used the TL method. The measurement procedure used with additive doses on quartz crystal grains. Measurement of dose by irradiation is done twice, at doses of 10 Gray (Gy) and 30 Gy while for annual dose is determined by analyzing the concentration of Uranium, Thorium, and Potassium using the X-ray fluorescence of method XRF.Two trend line is made to determine both minimum and maximum linear equation. Natural TL intensity shows 14380 arbitrary unit (a.u) and 14430 a.u as the minimum and maximum peak. Irradiated sample with 10 Gy dose shows peak at 1883â€“1947 a.u, and 30 Gy dose shows peak at 2733-2763 a.u. Regression trend line made by artificial dose show that natural TL intensity equivalent with 304.05-315.96 Gy. Calculation of uranium, thorium, potassium, water content, and beta factor produce annual dose in the amount of 0.5408 Gy. Through TL method, it is known that the absolute age of heat source at soppeng is 573 Â± 11 kilo age years old.